Factors shaping the implementation of the SAFE strategy for trachoma using the Consolidated Framework for Implementation Research: a systematic review. Issue 1 (1st January 2019) - Maritim, Patricia; Zulu, Joseph Mumba; Jacobs, Choolwe; Chola, Mumbi; Chongwe, Gershom; Zyambo, Jessy; Halwindi, Hikabasa; Michelo, Charles
ABSTRACT: Background : The SAFE strategy (surgery for trichiasis, antibiotics for active infection, facial cleanliness and environmental improvement) is the World Health Organization (WHO) recommended guideline for the elimination of blindness by trachoma by the year 2020. Objective : While evaluations on the implementation of the SAFE strategy have been done, systematic reviews on the factors that have shaped implementation are lacking. This review sought to identify these factors. Methods : We searched PUBMED, Google Scholar, CINAHL and Cochrane Collaboration to identify studies that had implemented SAFE interventions. The Consolidated Framework for Implementation Research (CFIR) guided development of the data extraction guide and data analysis. Results : One hundred and thirty-seven studies were identified and only 10 papers fulfilled the eligibility criteria. Characteristics of the innovation – such as adaptation of the SAFE interventions to suit the setting and observability of positive health outcomes from pilots – increased local adoption. Characteristics of outer setting – which included strong multisectoral collaboration – were found to enhance implementation through the provision of resources necessary for programme activities. When community needs and resources were unaccounted for there was poor compatibility with local settings. Characteristics of the inner setting – such as poor staffing, high labour turnovers and lack of ongoing training – affected health workers' implementation behaviour. Implementation climate within provider organisations was shaped by availability of resources. Characteristics of individuals – which included low knowledge levels – affected the acceptability of SAFE programmes; however, early adopters could be used as change agents. Finally, the use of engagement strategies tailored towards promoting community participation and stakeholder involvement during the implementation process facilitated adoption process. Conclusion : We found CFIR to be a robust framework capable of identifying different implementation determinants in low resource settings. However, there is a need for more research on the organisational, provider and implementation process related factors for trachoma as most studies focused on the outer setting.